Patient satisfaction: The importance of doctor-patient communication - Agostinho, Catarina (2010)
Objectives: To evaluate and understand which aspects of verbal and non-verbal communication patients refer as more satisfying. Type of Study: Cross-sectional Study Location: Centro Hospitalar Cova da Beira (CHCB) - Emergency Room Study Population: Patients attending the Emergency Room Methods: A questionnaire was applied by direct interview to 200 patients with 18 years-old or older, at the Emergency Room, during 10 random days, between November and December 2008. Results: Most participants referred that speed of speech (83.5%), visual contact (90%), physical closeness (68,5%) and doctors movements, such as nodding while listening patients complains (70%), are important for their satisfaction. On the other hand, they believe that doctors hair (78%), way of dressing (69,5%) and accent (68%) are irrelevant. When asked about more specific aspects of communication, they say they are more satisfied when the doctor speaks slowly (95,7%), as loud as them (87%) with common expressions (94,3%), dresses up in an informal manner (82,3%), touches them (67,5%), sits in front of them behind the desk (57,2%), and when female doctors have long (66,7%) and well combed hair (93,8%). When asked about the sex and age of the physician who contributes most to their satisfaction, patients show a preference for female physicians (75,7%); and by those who are under 50 years-old (70,1%). Conclusion: There are variables of verbal and non-verbal communication part of the doctor-patient relationship that influence the patients satisfaction.